THE INDICATORS OF MONETARY SECTOR SECURITY AS PART OF THE FINANCIAL SAFETY OF UKRAINE - N. Plieshakova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article examines the state of financial safety through its component – the security of the monetary sector.